Bright, dark and singular optical solitons in a power law media with fourth order dispersion - İnç, Mustafa; Ates, Esma (Springer, 2017)
This study focuses on exact solutions of nonlinear Schrodinger equation in a power law media with fourth order dispersion. Jacobi elliptic functions will be used to carry out the integration of this equation. Bright, dark and singular optical soliton solutions are obtained as well as Jacobi elliptic function solutions.
Keywords: Solitons; Jacobi elliptic functions; Fourth order dispersion